Contribution about the knowledge of Lepronyssoides pereirai (Fonseca, 1935) (Mesostigmata: Macronyssidae): hosts and distribution - de Oliveira, Glauber Meneses Barboza (2020)
The genus Lepronyssoides Fonseca comprises four Neotropical species associated mainly with rodents. One of these species, L. pereirai (Fonseca), has been recorded parasitizing rodents and marsupials in several states of the north, northeast, and central-west regions of Brazil. This study is based on samples housed at the Acari Collection of the Butantan Institute (IBSP) and the National Collection of Ectoparasites and Vectors of the Univasf (NCEV-Univasf, Petrolina, PE, Brazil). It includes the first record of L. pereirai for the states of Piauí, Mato Grosso do Sul, and new host-associations with Thrichomys pachyurus, T. laurentius and Oecomys cleberi.